Social Functioning of Persons with Disabilities Who Use Three-Wheeled Motorcycles - Khoirunnisa Virgiana Khan; Afina Medina Azaleya; Delfira Syelfiyola Rosadi; Alif Naafi Ardradhika (Asosiasi Dosen Muda Indonesia, 2025)
This study explores the social functioning of persons with disabilities who use modified three wheeled motorcycles as a means of mobility and daily activity support. Using a qualitative approach with a phenomenological perspective, the research examines lived experiences related to independence, social participation, and role fulfillment within the community. Data were collected through in depth interviews and observations, then analyzed thematically to identify recurring meanings and patterns. The findings indicate that the use of three wheeled motorcycles contributes positively to mobility autonomy, access to social interaction, and the ability to perform economic and social roles. The vehicle functions not only as a transportation tool but also as a symbol of independence and self confidence. However, several challenges remain, including technical limitations, environmental barriers, maintenance issues, and social perceptions. Overall, the study highlights the importance of accessible transportation in strengthening social functioning and emphasizes the need for supportive policies, inclusive infrastructure, and community awareness to enhance the quality of life of persons with disabilities.